Development of an Iron-Enriched Ekado as a Potential Food-Based Strategy for Anemia Prevention among Adolescent Girls - Annisa Rizkiriani; Firda Zavia Nabila; Ceasandra Ratu Syahtika; Alicia Siti Amanah; Ghina Noer Calliesna Putri; Ani Nuraeni; Vieta Annisa Nurhidayati (Journal of Indonesia Applied Nutrition (JIAN), 2026)
Iron deficiency anemia remains a major nutritional concern among adolescents, with a disproportionately higher prevalence in adolescent girls. Developing iron dense food products that are both nutritionally valuable and organoleptically acceptable represents a practical food based strategy to address this issue. This study aimed to formulate an ekado product incorporating chicken meat, chicken liver, and tofu as sources of iron and protein, and to evaluate its sensory acceptability and nutrient composition. A Completely Randomized Design was applied with three formulation variants F1 (43% chicken meat, 35% chicken liver, 22% tofu), F2 (50% chicken meat, 17% chicken liver, 33% tofu), and F3 (33% chicken meat, 17% chicken liver, 50% tofu). Sensory evaluation was conducted by 31 semi-trained panelists using a hedonic scale to assess color, texture, taste, and aroma. Statistical analysis was performed using the Kruskal Wallis test followed by the Mann Whitney post hoc test. The findings indicated that formulation F2 achieved significantly higher scores for color, texture, and taste (p < 0.05), while also obtaining the highest mean score for aroma, although the difference was not statistically significant. Nutrient analysis per serving (84 g) of F2 revealed an energy content of 408 kcal, 14.8 g protein, 35 g fat, 10 g carbohydrates, and 4.1 mg iron. This iron content contributes approximately 27.3% of the recommended daily iron intake for adolescent girls Based on these results, F2 was identified as the optimal formulation and demonstrates potential as a food based alternative to support adequate daily iron intake among adolescent girls.